Kemajuan Ilmu Pengetahuan di Andalusia : Jembatan Penuntun Penerang Kehidupan - Muhammad Daffa Pratama; Fanisa Putri Anggraini; Sabitah Salwa AlFarras; Hudaidah Hudaidah; Risa Marta Yati (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study discusses the progress of science in Andalusia during the rule of the Umayyad Daulah II, which served as an essential bridge between the Islamic world and the West. The purpose of this research is to examine the factors that stimulated scientific advancement, the fields of knowledge that developed, and the intellectual values inherited for modern life. This study employs a qualitative approach with a library research method by analyzing various historical sources, academic journals, and scholarly works related to Islamic civilization in Andalusia. The results show that scientific progress in Andalusia under the Umayyad Daulah II emerged from political stability, social tolerance, religious enthusiasm, and government support for education and research. Knowledge flourished in diverse disciplines such as medicine, astronomy, mathematics, philosophy, art, and architecture. Andalusia became a leading center for education and translation, transmitting Islamic knowledge to Europe and contributing greatly to the rise of the Renaissance. In conclusion, the intellectual achievements of Andalusia demonstrate that the harmony between faith, justice, and openness produces a just and progressive civilization. These scientific and moral values remain relevant for guiding the development of a modern civilization grounded in ethics and humanity.